Review of available SW solutions for intellectual property management systems from the perspective of open innovation - Ondrej Krejcar; Robert Frischer; Robert Hlavica; Kamil Kuca; Petra Maresova; Ali Selamat (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
This piece of research is focused on providing a review of the software solutions that exist when it comes to mechanisms that govern the management of intellectual property. It takes a deeper look at requirements within the university transfer office domain. Universities are a genuine source of knowledge. They have been identified not just as knowledge hubs but also as the spaces where innovations are born. These innovations then make their way into the market through the different industries they serve, becoming products that gain the attention of actual consumers. Given the magnitude of the innovations being developed in different universities around the world, it is imperative that mechanisms for the safety of this knowledge also be put into place. The world has evolved into a knowledge economy, where knowledge is an asset and something that can create profitability. This means that not protecting the knowledge that is being created can only lead to a loss in the future. Managing intellectual property, therefore, is not only a matter of procedure but one of great importance. Solutions that are easily accessible, cost-effective, and time-effective are essential. Thus, the goal of this article is to provide an overview of existing software (SW) solutions suitable for managing technology and knowledge transfer at universities based on requirements from the technology transfer office at university and specified using the model of the whole process from inventor until patent office. University Technology Transfer (TT) is a bit different in comparison to TT at companies. This gap is shown in the article using modelling of process, states, and class diagrams of a university Technology Transfer Office (TTO). Based on process definition and TTO responsibilities, a review of available SW solutions is done for 10 selected examples, as well as a related literature analysis. Findings and implications are summarized at the end of article in the context of specific needs of a university TTO, while major implications are shown as a problem of priority definition of every university TTO, namely, in the sense of value of SW solutions for intellectual property (IP) management, reporting possibilities, and representing IP and know-how.
Keywords: 650; management; open innovation; intellectual property; knowledge; patent; software; technology transfer